Impact of Training Programmes on Knowledge and Adoption of Organic Farming Practices (Global Journal of Science Frontier Research, 2016)
Organic farming is a production system which avoids or largely excludes the use of synthetic compounded fertilizers, pesticides, growth regulators and livestock feed additives. This study was conducted purposively in Bhanjanagar and Jagannathprasad blocks of Ganjam district due to maximum number of trained farmers in organic farming. The total 120 trained farmers were selected for the study. Only 7.50 per cent of the respondents had high knowledge in organic farming before participation in training and after the participation in training this figure increased up to the 26.67 per cent. All the selected attributes of the trained farmers, except age, caste and size of family were found having significant relationship with their knowledge level on organic farming. High cost of inputs & difficult methods for preparation were major constraints experienced by the farmers.
Keywords: impact assessment; training programmes; knowledge and organic farming